2020
DOI: 10.1093/asjof/ojaa048
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction Survey of Women After Cosmetic Genital Procedures: A Cross-Sectional Study From Saudi Arabia

Abstract: Background Female cosmetic genital surgery (FCGS) aims for better aesthetic genital appearance and improved functional aspects, to enhance women’s self-esteem and satisfaction. Objectives This study aims to assess the satisfaction of women who have undergone FCGS, and its impact on their sexual, psychological, and aesthetic aspects. Methods An observational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Social media certainly contributed the most to this rise in awareness; Crockett et al conducted a study on the influence of plastic surgery, and they discovered that television shows influenced four out of five patients to seek cosmetic surgery [6]. All the studies that were conducted in Saudi Arabia targeted the patients' satisfaction, the perspective of their experience after the operation, and their motives [7]. However, several studies evaluated physicians' knowledge from different subspecialties, and the reported knowledge level was suboptimal, but their attitudes improved [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Social media certainly contributed the most to this rise in awareness; Crockett et al conducted a study on the influence of plastic surgery, and they discovered that television shows influenced four out of five patients to seek cosmetic surgery [6]. All the studies that were conducted in Saudi Arabia targeted the patients' satisfaction, the perspective of their experience after the operation, and their motives [7]. However, several studies evaluated physicians' knowledge from different subspecialties, and the reported knowledge level was suboptimal, but their attitudes improved [8,9].…”
Section: Introductionmentioning
confidence: 99%